Adolescents with different profiles of scientific versus artistic creativity: Similarity and difference in cognitive control. (September 2020) - Zhang, Xinru; Cheng, Lifang; Dai, David Y.; Tong, Weishan; Hu, Weiping
Highlights: Scientifically creative students have better cognitive inhibition than artistic talents Adolescents with high scientific creativity show better response inhibition than those with high artistic creativity Creative students in science and arts both share a good switching function More creative students perform better on all three functions, regardless of domain Abstract: This study aimed to compare performance of cognitive control functions by junior high school students with different profiles of scientific vs. artistic creativity. A total of 297 Chinese junior high school students were tested with a battery of scientific and artistic creativity tests. Out of this sample, 110 students who ranked in the top 27 % or bottom 27 % on scientific and artistic creativity were selected to form four groups, and their performance on cognitive inhibition, response inhibition, and switching was compared. Results showed that scientifically creative students had better cognitive inhibitory and response inhibitory ability than artistically creative students, but no significant difference existed between them in switching. The findings expand our knowledge of cognitive characteristics of students with different domain strengths with the following practical implications: high cognitive and response inhibition may be desirable characteristics for identifying and developing scientific talent but it may be less central for identifying and developing artistic talent.